Immune Tolerant Chronic Hepatitis B: The Unrecognized Risks - Kennedy, Patrick T. F. (Viruses, 2017)
Chronic infection with hepatitis B virus (HBV) progresses through multiple phases, including immune tolerant, immune active, immune control, and, in a subset of patients who achieve immune control, reactivation. The first, the immune tolerant phase, is considered to be prolonged in duration but essentially benign in nature, lacking long-term consequences, and thus not recommended for antiviral therapy. This review challenges the notion that the immune tolerant phase is truly benign and considers the possibility that events during this phase may contribute significantly to cirrhosis, hepatocellular carcinoma (HCC), and the premature death of 25% of HBV carriers worldwide. Thus, earlier treatment than recommended by current guidelines should be considered. Low therapeutic coverage exacerbated by restrictive treatment guidelines may facilitate disease progression in many patients but also increase the risk of neonatal and horizontal transmission from untreated mothers to their children. While a prophylactic vaccine exists, there are many areas worldwide where the treatment of adults and the delivery of an effective vaccination course to newborns present difficult challenges.